Atomically smooth gallium nitride surface prepared by chemical-mechanical polishing with S2O82−-Fe2+ based slurry. (June 2017) - Shi, Xiaolei; Zou, Chunli; Pan, Guoshun; Gong, Hua; Xu, Li; Zhou, Yan
Abstract: In this paper, a significant improvement of chemical-mechanical polishing on gallium nitride with S2 O8 2 − -Fe 2+ based slurry is presented in detail. The results indicate that the S2 O8 2 − -Fe 2+ additives possessed obvious effect to enhance the polishing efficiency of GaN, and successfully achieved good surface quality after polishing. The addition of complexing agent obviously improves the stability of catalytic system. Besides, we also studied the special change rule of atomic step-terrace topography from the surface of GaN to describe the material removal mechanism during CMP process. The results show that the removal of materials by CMP follows rigid rules, which may help to improve the material removal mechanism of CMP. Highlights: We achieved a high MRR of 120 nm/h for CMP of GaN by using S2 O8 2− -Fe 2+ additives. We obtain atomic-level smooth surface by S2 O8 2− -Fe 2+ additives and advanced AFM technique. We demonstrate the special change rule of terraces topography from the surface of GaN.